Industrial training programme: what matters most? / Syadiyah Abdul Shukor. - Abdul Shukor, Syadiyah (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
This study aims to explore business administration students’ expectation and perception towards their industrial training programme. A quantitative research using survey questionnaire was conducted. A total of 96 completed survey questionnaires were received and analysed. Students reported positive feedback on most aspects of the industrial training except for interesting and challenging work and good opportunity for future employment in the same company. The faculty needs to improve certain aspects of the industrial training programme to ensure effective planning and implementation of industrial training programme among business administration students. This study provides practical information on how faculties offering business administration programmes can incorporate industrial training component in the programme structure more effectively.